03. Immunogenicity and Safety of a Quadrivalent Meningococcal Conjugate Vaccine (MenACYW-TT) Administered as a Booster Dose in Adults and Adolescents Vaccinated Against Meningococcal Disease 3 - 6 Years Earlier. (4th December 2021) - Peterson, James; Deseda, Carmen; Julien, Katie; Zambrano, Betzana; Áñez, Germán; Jiayuan, Sue; Pan, Judy; Arroum, Habiba; Varghese, Kucku; Jordanov, Emilia; Dhingra, Mandeep S
Abstract: Background: Booster doses of meningococcal conjugate vaccines may induce long-term protection against invasive meningococcal disease. MenACYW-TT [MenQuadfi ® ] is a quadrivalent meningococcal conjugate vaccine, licensed for use in ages 2 years and older in USA. The vaccine is also licensed in ages 12 months and older in EU and other countries. Methods: A phase IIIb study (NCT04084769) was conducted to evaluate the persistence of immune response in adults and adolescents primed 3-6 years earlier with either MenACYW-TT or MCV4-CRM (Menveo ® ) and, safety and immunogenicity of MenACYW-TT when administered as a booster dose with or without concomitant administration with MenB vaccines (Bexsero ® and Trumenba ® ). Serum bactericidal assays with human complement (hSBA) and baby rabbit complement (rSBA) were used to measure antibodies against vaccine serogroups at baseline (Day 0 [D0]), D06 (in a subset) and 30 days post-vaccination (D30). Safety data were collected up to 6 months post-vaccination. Results: At D0, the GMTs were higher in subjects primed with MenACYW-TT vs MCV4-CRM for serogroups C, Y and W, and were comparable for serogroup A. At D0, all hSBA GMTs were higher than those observed pre-priming dose, suggesting persistence of immunity. Sufficiency of hSBA seroresponse ( >75%) was demonstrated following administration of MenACYW-TT booster dose regardless of the priming vaccine administered 3-6 years earlier. Vaccine seroresponse in a subset of participants at D06 ranged from 77.8% (95%CI 62.9%; 88.8%) for serogroup A to 97.8% (88.5%; 99.9%) for serogroup W suggesting a quick onset of immune response post-booster. Post-vaccination (D30) hSBA GMTs were comparable for serogroups A, Y and W regardless of the nature of the priming vaccine and were higher for serogroup C in subjects primed with MenACYW-TT vaccine. The MenACYW-TT booster dose was well-tolerated and had similar safety profiles regardless of the priming vaccine. The safety profiles were comparable regardless of the MenB vaccine co-administered with MenACYW-TT vaccine. Conclusion: MenACYW-TT used as priming vaccine was able to demonstrate persistence of immune response 3-6 years later. MenACYW-TT elicits robust booster responses in adults and adolescents primed with MenACYW-TT or MCV4-CRM Disclosures: Betzana Zambrano, MD, Sanofi Pasteur (Employee) Germán Áñez, MD, Sanofi Pasteur (Other Financial or Material Support, Former employee) Sue Jiayuan, MSc, Sanofi Pasteur (Independent Contractor) Judy Pan, PhD, Sanofi Pasteur (Employee) Habiba Arroum, MD, Sanofi Pasteur (Employee) Kucku Varghese, PhD, Sanofi Pasteur (Employee) Emilia Jordanov, MD, Sanofi Pasteur (Employee, Shareholder) Mandeep S. Dhingra, MD, Sanofi Pasteur (Employee, Shareholder)